HUBUNGAN OBESITAS SENTRAL DENGAN PROFIL LIPID PADA ORANG DEWASA UMUR 25-65 TAHUN DI KOTA BOGOR (Baseline Studi Penyakit Tidak Menular di Kota Bogor, Jawa Barat) - Sudikno, Sudikno; Syarief, Hidayat; Dwiriani, Cesilia Meti; Riyadi, Hadi; Pradono, Julianti (GIZI INDONESIA, 2016)
The global epidemic of obesity is rapidly becoming a major public health problem in many countries of the world. Rapidly changing diets and lifestyles are trigger to the global obesity epidemic. This study aimed to determine the prevalence of central obesity and the relationship between central obesity and lipid profile in adults aged 25-65 years. This study used baseline data "Cohort Study of Non-Communicable Diseases" that was carried out in 2011-2012 in Bogor City, West Java Province. The study design was cross-sectional. A number of samples analyzed were 4554 subjects. Result of the analysis showed that the prevalence of central obesity was found 51.3 percent. The portion of subjects with high total cholesterol levels was 16 percent. The percentage of high LDL cholesterol levels was 17.6 percent. While the portion of low HDL cholesterol levels was 16.2 percent and the portion of high triglyceride levels was 8.5 percent. The results of logistic regression analysis showed that central obesity in adults aged 25-65 associated with lipid profile after controlling the variables of sex, age, and smoking habits. The need for preventive measures to prevent central obesity and abnormal lipid profiles evolve toward disease complications through the fulfillment of adequate daily physical activity and healthy eating habits.